Postcolonial encounters between the west, the east, and Islam in Hanum Salsabiela’s travel writing - Rahmawati, Risma Nur; Faruk, Faruk; Udasmoro, Wening (Universitas Ahmad Dahlan, 2025)
Travel writing serves as a crucial medium through which narrators document and interpret their encounters with foreign cultures. This study examines Hanum Salsabiela’s Bulan Terbelah di Langit Amerika (BTLA) to explore how the narrator reports on the United States, expresses her self-identity during her journey in the United States, and represents the people of the United States through the lens of postcolonial travel writing. This research is significant because the narrator not only depicts the United States as a geographical and cultural space but also highlights the presence of Islam within it. As the country with the largest Muslim population in the world, it is not surprising that many Indonesian travel writers are drawn to Islamic regions such as the Middle East. However, in recent years, some have begun to explore Western countries, which differ significantly in culture and religion. The data collection methods used in this research are textual observation and note-taking. In addition, the data analysis employs discourse analysis grounded in the postcolonial travel writing paradigms of Carl Thompson. In conclusion, the study indicates that the United States is portrayed as a metropolitan country, yet it continues to face overlapping social issues, including homelessness, Islamophobia, and discrimination. BTLA functions as self-reflective travel writing, using the United States as a space for the narrator to explore and reflect on her identity as a Muslim. Furthermore, in representing the Other, the narrator still exhibits traces of a neo-colonial attitude, even though she strives to present a cosmopolitan perspective.